Characteristics of Patients with Low Back Pain among Healthcare Professionals at John Piet Wanane General Hospital: A Cross-Sectional Study - Lu Jordy Luhur; Agustinus Ruma; Paulus Sugianto (AKSONA, 2022)
Highlight: Healthcare professionals have a higher risk of suffering LBP than other industrial workers. Adult women who have a high body mass index are likely to experience LBP. Healthcare professional should maintain a healthy lifestyle to increase productivity and decrase mortality   ABSTRACT Introduction: Low back pain (LBP) is musculoskeletal pain, tension, or stiffness that occurs below the costal margin and above the inferior gluteal folds, with or without sciatica. It has been found that healthcare professionals are more likely to experience LBP than other industrial workers. Many factors contribute to higher rates of LBP, including occupation, age, obesity, family history, lack of exercise, and psychosocial condition. Objective: To determine LBP’s prevalence and risk factors among healthcare professionals at John Piet Wanane General Hospital. Methods: This is a cross-sectional study that included 158 healthcare professionals. The data was collected using questionnaires and analyzed using univariate and multivariate logistic regression. Results: The overall prevalence of LBP in this study was 62.7%. Descriptive statistics showed that LBP was most common in the female group (71.7%), age group 35-50 years (52.5%), overweight group (61.6%), married group (80.8%), never or rarely exercise group (84.8%), non-smoking group (85.9%), non-drinkers group (84.8%), and moderate perceived stress group (63.6%). Multivariate logistic regression analysis showed that BMI was significantly associated with LBP. Compared with underweight participants, overweight participants were four times more likely to experience LBP (OR = 4.344, 95% CI: 1.297-14.552). Conclusion: This study demonstrates a high prevalence of LBP among healthcare professionals. High BMI, especially being overweight, increases the risk of developing LBP. Overweight and obesity among healthcare professionals may affect their credibility in providing patients with healthy nutrition and exercise advice. Healthcare professionals should maintain a healthy lifestyle to increase productivity and decrease mortality.